Peristaltic Transport for Fractional Generalized Maxwell Viscoelastic Fluids through a Porous Medium in an Inclined Channel with Slip Effect - Z. Hummady, Lika; M. Abdulhadi, Ahmed (Iraqi Journal of Science, 2023)
In this paper we present a study on Peristaltic of fractional generalized Maxwell viscoelastic fluid through a porous medium. A modified Darcy-Brinkman model is utilized to simulate the flow of a generalized Maxwell fluid in a porous medium in an inclined channel with slip effect. The governing equation is simplified by assuming long wavelength and low Reynolds number approximations. The numerical and approximate analytical solutions of the problem are obtained by a semi-numerical technique, namely the homotopy perturbation method. The influence of the dominating physical parameters such as fractional Maxwell parameter, relaxation time, amplitude ratio, permeability parameter, Froude number, Reynolds number and inclination of channel on the flow characteristics are depicted graphically.